The Role of Tropical Atlantic in ENSO Predictability Barrier. Issue 7 (10th April 2023) - Zhao, Yingying; Jin, Yishuai; Capotondi, Antonietta; Li, Jianping; Sun, Daoxun
Abstract: This paper investigates the impacts of tropical Atlantic on El Niño‐Southern Oscillation (ENSO) predictability through an empirical dynamical model‐ Linear Inverse Model (LIM). By selectively including or excluding the coupling between tropical Atlantic and tropical Pacific in LIM, we find that the tropical Atlantic dynamics significantly improve the Eastern Pacific (EP)‐ENSO prediction and weaken the EP‐ENSO predictability barrier (PB), with the Equatorial Atlantic (EA) mode playing a more important role than the Tropical North Atlantic (TNA) mode. The tropical Atlantic impacts on Central Pacific (CP)‐ENSO predictability and PB are relatively smaller. Consistent with observations, the tropical Atlantic can weaken PB in most CMIP6 models. The evolution of the tropical Atlantic optimum initial structures confirms the important influence of the EA mode on the eastern tropical Pacific. Therefore, the tropical Atlantic dynamics, especially the EA mode, should be appropriately considered to improve the prediction of EP‐ENSO and weaken the EP‐ENSO PB. Plain Language Summary: El Niño–Southern Oscillation (ENSO) is one of the dominant climate modes in the tropical Pacific on interannual timescales, with significant global impacts. The tropical Atlantic sea surface temperature (SST) variability, especially in the tropical North Atlantic (TNA) and equatorial Atlantic (EA), is shown to have important impacts on ENSO variability. Using a linear dynamical model, we find that including the dynamics of the tropical Atlantic, especially the EA SST mode, can significantly improve the forecast skill of Eastern Pacific ENSO and weaken the EP‐ENSO spring predictability barrier (SPB), which is a sudden reduction of ENSO prediction skill in the boreal spring. However, Central Pacific (CP)‐ENSO's forecast skill is less influenced by the tropical Atlantic dynamic. Consistent with the observations, the topical Atlantic can weaken ENSO SPB in most CMIP6 climate models. Our results suggest that the tropical Atlantic dynamics should be appropriately considered to improve the forecast skill of EP‐ENSO. Key Points: A linear dynamical model is used to study the impact of the tropical Atlantic on El Niño‐Southern Oscillation (ENSO) predictability Tropical Atlantic dynamics can improve Eastern Pacific (EP)‐ENSO predictability and weaken EP‐ENSO spring predictability barrier while the impact on Central Pacific‐ENSO is limited The Equatorial Atlantic mode plays an important role in the tropical Atlantic influence of EP‐ENSO prediction